2009
DOI: 10.1093/bioinformatics/btp174
|View full text |Cite
|
Sign up to set email alerts
|

Variable slope normalization of reverse phase protein arrays

Abstract: Code to implement the method in the statistical package R and anonymized data are available at (http://bioinformatics.mdanderson.org/supplements.html).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 32 publications
1
73
0
Order By: Relevance
“…34 The loading control 35 and topographical normalization procedures accounted for variations in protein concentrations and background staining. Normalization procedures were performed using the R software program (Version 2.…”
Section: Discussionmentioning
confidence: 99%
“…34 The loading control 35 and topographical normalization procedures accounted for variations in protein concentrations and background staining. Normalization procedures were performed using the R software program (Version 2.…”
Section: Discussionmentioning
confidence: 99%
“…36 Loading control 37 and topographical normalization procedures accounted for protein concentration and background staining variations. Analysis using unbiased clustering and perturbation bootstrap clustering, and principle component analysis was then performed as described previously.…”
Section: Discussionmentioning
confidence: 99%
“…Neely et al (Neeley et al, 2009) processed clinically similar ALL samples in two batches and observed differences in their protein data distributions. There were additive and multiplicative effects in the data that could not be accounted by biological or sample loading differences.…”
Section: Star*methodsmentioning
confidence: 99%